Socio-demographic and lifestyle factors associated with folate status among non-supplement-consuming Canadian women of childbearing age - Shi, Yipu (Can J Public Health, 2014)
Objective: Mandatory folic acid fortification was implemented in Canada in 1998 to reduce the risk of neural tube defects (NTD). Our objective was to assess the relationship between socio-demographic factors and folate status in non-supplement-consuming Canadian women of childbearing age. METHODS: Data on demographic factors, lifestyle factors, physical measures and red blood cell (RBC) folate concentration were collected from 1,008 non-supplement-consuming women aged 15-49 years in the Canadian Health Measures Survey (2007–2009). RBC folate ≥906 nmol/L was used as a cut-off for optimal folate status for protection from NTD. RESULTS: Approximately 75% of non-supplement consuming women had an RBC folate concentration ≥906 nmol/L. Young age (15-19 years), White ethnicity, less than secondary education, lowest income adequacy, smoking and high body mass index were associated with a higher prevalence of lower folate status. After adjustment, only young age (adjusted odds ratio [OR] 1.99–95% confidence interval [CI]: 1.25–3.18) was associated with lower folate status. Less than secondary education (adjusted OR 5.66, 95% CI: 1.10–29.04) and lowest income adequacy (adjusted OR 4.77, 95% CI: 1.06–21.49) were associated with lower folate status in women aged 15-24 and 25-49 years, respectively. CONCLUSIONS: Many risk factors for lower folate status identified before food fortification was implemented were not associated with folate status in our representative sample of non-supplement-consuming Canadian women. However, younger women, women aged 15-24 with less than secondary education and women aged 25-49 with low income adequacy remain at risk of lower folate status, supporting the continued promotion of folic acid supplement use to women of childbearing age.